2017
DOI: 10.1016/j.msea.2017.03.073
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical evolution and thermal stability of microstructure with deformation twins in 316 stainless steel

Abstract: We report extensive nano-twin formation in 316 stainless steel (SS) and the evolution of a hierarchical microstructure through the formation of multi-scale twin bundles after uniaxial tension with uniform elongation levels of 20%, 30%, and 40%. Multiscale characterization techniques were employed to reveal the nature of these twins. The twin density increases with the increasing strain level, however, the twin width remains the same, notably reducing the mean free path of dislocations. Concurrently, significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…(2) The increase of SHR in stage II is possibly due to formation of deformation twinning [4,5]. In this stage prevention of cross slip can cause early onset of twinning, leading to further hardening of material [39]. In parallel with straining, grain size gets smaller as twins fragment the grains into smaller grains with different crystallographic orientations [9,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) The increase of SHR in stage II is possibly due to formation of deformation twinning [4,5]. In this stage prevention of cross slip can cause early onset of twinning, leading to further hardening of material [39]. In parallel with straining, grain size gets smaller as twins fragment the grains into smaller grains with different crystallographic orientations [9,49].…”
Section: Discussionmentioning
confidence: 99%
“…In order to eliminate topographical stimuli on cells, two sets of samples were prepared, where only one of them was polished post-mortem down to 1 μm with diamond abrasives (hereafter named as polished-samples) Then, these samples were etched at ambient temperature for 3 min in a solution of 10 ml nitric acid, 30 ml hydrochloric acid and 30 ml distilled water to reveal the activated mechanisms [39]. The microstructural evolution of the samples was observed via optical microscope (OM) in DIC mode and field-emission scanning electron microscope (SEM) with inlens SE (secondary electron) detector under an accelerating voltage of 10 kV.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary twins may be nucleated within the twins of the primary system [28]. Wang et al [29] observed the microstructure evolution in 316 stainless steel in a range of deformation levels: 10-30%. Deformation features evolved from planar dislocations to a single system twinning, then to multi-system twinning and intersections among twins, with increasing strain.…”
Section: Microstructure Changes During Interrupted Tensile Testsmentioning
confidence: 99%
“…In this way, ultrafine-grained materials look very attractive due to superior strength properties but, having a high-volume fraction of intergranular boundaries, they simultaneously possess limited plasticity and thermal stability compared to coarse-grained counterparts [8,9,12]. GBE could be the possible way to make the ultrafine-grained materials more stable against recrystallization during post-deformation heat treatment, via producing of low-energy coherent special boundaries, for instance, twin-assisted Σ3 n boundaries [13][14][15][16]. For nanotwinned 330SS (stainless steel), Zhang and Misra [13] demonstrated a superior thermal stability of coherent twin boundaries, as microstructure of a Fe-22.3Mn-0.19Si-0.14Ni-0.27Cr-0.61C TWIP steel, due to formation of deformation microbands and twins during equal channel angular pressing at elevated temperatures (200 • C, 300 • C, and 400 • C) [32].…”
Section: Introductionmentioning
confidence: 99%